Pro-Inflammatory Markers in Serum and Saliva in Periodontitis and Hypertension - Teodora Bolyarova; Lyubomir Stefanov; Emilia Naseva; Konstantin Stamatov; Samuil Dzhenkov; Blagovest Stoimenov; Ralitsa Pancheva; Nikolay Dochev; Nikolay Ishkitiev (Medicina, 2025)
Background and Objectives: Over the past few decades, a substantial body of evidence has linked periodontitis to systemic diseases—including hypertension—but the mechanisms underlying this association are not fully understood. This study aims to identify the factors that may mediate this relationship, including an analysis of the inflammatory biomarker NLRP3 and IL-1β levels in serum and saliva in patients with both diseases. Materials and Methods: This study included 108 individuals (mean age, 47.8 years, SD 12.8), 38.9% male and 61.1% female. The participants were divided into four groups: Group I—26 healthy participants; Group II—24 participants with periodontitis; Group III—26 participants with hypertension; and Group IV—32 participants with both periodontitis and hypertension. Clinical examinations were performed to diagnose hypertension and periodontitis, including a survey and blood tests in all patients. NLRP3 and IL-1β levels in serum and saliva were measured using ELISA. Results: Patients with periodontitis and hypertension were significantly older than those without these conditions (respectively, p < 0.001 and p < 0.001) and had more missing teeth (respectively, p < 0.001 and p = 0.037). Higher values were found in the periodontitis and hypertension group than in healthy individuals for VLDL (p = 0.001), triglycerides (p = 0.001), CRP (p = 0.003), WBC (p = 0.007), blood sugar (p = 0.002), total cholesterol (p = 0.003), and LDL (p = 0.010). Significantly higher levels of NLRP3 in saliva (p = 0.038) and serum (p = 0.021) were observed in patients with periodontitis than in those without periodontitis. Significant correlations were found between serum NLRP3 levels and the presence of hypertension (p = 0.001) and between saliva IL-1β levels and the presence of hypertension (p = 0.010). Serum NLRP3 levels demonstrated a predictive value for hypertension (AUC 0.693, 95% CI 0.590–0.796, and p = 0.001), with an established cutoff value of 0.68 ng/mL (sensitivity 0.623, specificity 0.630). Conclusions: The higher levels and correlations of pro-inflammatory markers in serum and saliva observed in patients with periodontitis and hypertension support the hypothesis of a relationship between these diseases, likely mediated by low-grade systemic inflammation.